Image analysis in the evaluation of the physiological potential of maize seeds - Pinto, Crislaine Aparecida; Carvalho, Maria Laene; Andrade, Dayliane; Leite, Eva; Chalfoun, Igor (Revista Ciência Agronômica, 2015)
The Seed Analysis System (SAS) is used in the image analysis of seeds and seedlings, and has the potential for use in the control of seed quality. The aim of this research was to adapt the methodology of image analysis of maize seedlings by SAS, and to verify the potential use of this equipment in the evaluation of the physiological potential of maize seeds. Nine batches of two maize hybrids were characterised by means of the following tests and determinations: germination, first count, accelerated ageing, cold test, seedling emergence at 25 and 30ºC, and speed of emergence index. The image analysis experiment was carried out in a factorial scheme of 9 batches x 4 methods of analysis of the seedling images (with and without the use of NWF as substrate, and with and without manual correction of the images). Images of the seedlings were evaluated using the average lengths of the coleoptile, roots and seedlings; and by the automatic and manual indices of vigour, uniformity and growth produced by the SAS. Use of blue NWF afffects the initial development of maize seedlings. The physiological potential of maize seeds can be evaluated in seedlings which are seeded on white paper towels at a temperature of 25 °C and evaluated on the third day. Image analysis should be carried out with the SAS software using automatic calibration and with no correction of the seedling images. Use of SAS equipment for the analysis of seedling images is a potential tool in evaluating the physiological quality of maize seeds.